AtKC1 and CIPK23 Synergistically Modulate AKT1-Mediated Low-Potassium Stress Responses in Arabidopsis . Issue 4 (1st February 2016) - Wang, Xue-Ping; Chen, Li-Mei; Liu, Wen-Xin; Shen, Li-Ke; Wang, Feng-Liu; Zhou, Yuan; Zhang, Ziding; Wu, Wei-Hua; Wang, Yi
Abstract : Protein kinase CIPK23 and channel subunit AtKC1 are both crucial for the modulation of potassium channel AKT1 as well as for the response to low-potassium stress. Abstract: In Arabidopsis ( Arabidopsis thaliana ), the Shaker K + channel AKT1 conducts K + uptake in root cells, and its activity is regulated by CBL1/9-CIPK23 complexes as well as by the AtKC1 channel subunit. CIPK23 and AtKC1 are both involved in the AKT1-mediated low-K + (LK ) response; however, the relationship between them remains unclear. In this study, we screened suppressors of low-K + sensitive [ lks1 ( cipk23 )] and isolated the suppressor of lks1 ( sls1 ) mutant, which suppressed the leaf chlorosis phenotype of lks1 under LK conditions. Map-based cloning revealed a point mutation in AtKC1 of sls1 that led to an amino acid substitution (G322D) in the S6 region of AtKC1. The G322D substitution generated a gain-of-function mutation, AtKC1 D, that enhanced K + uptake capacity and LK tolerance in Arabidopsis. Structural prediction suggested that glycine-322 is highly conserved in K + channels and may function as the gating hinge of plant Shaker K + channels. Electrophysiological analyses revealed that, compared with wild-type AtKC1, AtKC1 D showed enhanced inhibition of AKT1 activity and strongly reduced K + leakage through AKT1 under LK conditions. In addition, phenotype analysis revealed distinct phenotypes of lks1 and atkc1 mutants in different LK assays, but the lks1 atkc1 double mutant always showed a LK -sensitive phenotype similar to that of akt1 . This study revealed a link between CIPK-mediated activation and AtKC1-mediated modification in AKT1 regulation. CIPK23 and AtKC1 exhibit distinct effects; however, they act synergistically and balance K + uptake/leakage to modulate AKT1-mediated LK responses in Arabidopsis.